Implant surface selection in primary cosmetic breast augmentation: A national cross-sectional study of UK plastic surgeons - Chloe Jordan; Krzysztof Sosnowski; Rushabh Shah; Charles Malata (JPRAS Open, 2025)
Introduction: Breast augmentation remains one of the most common cosmetic surgical procedures globally yet implant surface preference (textured versus smooth) remains a key area of debate. Whilst textured implants have traditionally been favoured in the UK and Europe, concerns around breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) and the absence of formal guidelines have contributed to wide variations in practice. This study therefore examines current UK practice among plastic surgeons, focusing on surgeon preferences and the factors guiding decision-making. Methods: An anonymised online survey was distributed to UK consultant plastic surgeons performing cosmetic breast augmentation. Data collected included implant surface, brand, incision, pocket, case volume, and ranked decision-making factors. Free-text responses were analysed thematically. Descriptive statistics and chi-square testing were used to explore associations. Results: Seventy-five consultant plastic surgeons responded (response rate = 31.3 %). Textured implants were most commonly used (82.7 %), although smooth implants were more frequently selected by high-volume surgeons (>50 cases/year, χ²(5) = 11.79, p = 0.038, Cramér’s V = 0.37). Mentor was the preferred brand (53.3 %), while Motiva was more commonly selected by smooth implant users (χ²(5) = 58.3, p = 0.011, Cramér’s V = 0.29). All surgeons preferentially used inframammary incisions; subglandular placement was most common (54.7 %). The top four decision-making factors in implant surface selection were patient preference, cosmetic outcome, risk of capsular contracture and BIA-ALCL possibility. Qualitative themes highlighted the influence of patient expectations, safety concerns, and institutional policy. Conclusion: UK practice in cosmetic breast augmentation remains varied. Although most surgeons preferred textured implants, a shift towards smooth implants appears to be emerging among high-volume operators.